2011
DOI: 10.1097/iae.0b013e31820d3cd2
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreally Implantable Voriconazole Delivery System for Experimental Fungal Endophthalmitis

Abstract: The therapeutic effect of intravitreal VCZ DDS on fungal endophthalmitis appears to be significantly better than intravitreal injection of VCZ. The optimal dose of VCZ in the DDS in this study was 1.2 mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…A literature review indicated that few drug delivery systems have been developed and their efficacy evaluated in animals. In one attempt, the therapeutic effect demonstrated by an intravitreal drug delivery system of voriconazole was superior to intravitreal injection in rabbits [ 7 ]. Chitosan nanoparticles containing daptomycin were developed in ocular treatment of bacterial endophthalmitis.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review indicated that few drug delivery systems have been developed and their efficacy evaluated in animals. In one attempt, the therapeutic effect demonstrated by an intravitreal drug delivery system of voriconazole was superior to intravitreal injection in rabbits [ 7 ]. Chitosan nanoparticles containing daptomycin were developed in ocular treatment of bacterial endophthalmitis.…”
Section: Introductionmentioning
confidence: 99%
“…This, in part, could be due to limited or unavailability of appropriate fungal endophthalmitis animal models. However, few earlier studies have utilized guinea pig [21] and rabbit [22,23] models to test the therapeutic efficacy of antifungal agents in Aspergillus fumigatus (AF) endophthalmitis. Similarly, we evaluated isavuconazole for the treatment of AF endophthalmitis in a mouse model [11].…”
Section: Introductionmentioning
confidence: 99%
“…68 Future options for the treatment of Pseudallescheria endophthalmitis could include the use of these compounds, possible combinations of existing antifungal agents, or even novel antifungal delivery devices for fungal endophthalmitis like the use of polylactic-coglycolic acid polymers. 69 In summary, Pseudallescheria endophthalmitis is a devastating condition that is more common than previously described. To ensure the overall care of the patient, involvement of infectious disease specialists and other physicians is crucial.…”
Section: Pseudallescheria Endophthalmitis Moloney and Parkmentioning
confidence: 95%